2020
DOI: 10.3389/fphar.2019.01679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multi–Target Neuroprotective Chemical Space of Benzofuran Scaffolds: A New Strategy in Drug Development for Alzheimer’s Disease

Abstract: against multiple events involved in AD. This benzofuran chemical framework will establish a multi-target chemical space that could set the basis for the development of super drugs against AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Our results aligned with this study, and it can be suggested that the selective activity might be related to the structure–activity relationship (SAR) of these phlorotannins to Aβ42 oligomers, notably to the fucofuroeckols containing the additional benzofuran ring compared with eckols. This is supported by previous studies demonstrating that benzofuran derivatives have neuroprotective properties against Aβ (Rizzo et al ., 2008; González‐Ramírez et al ., 2018; Lee & Byun, 2018; Cabrera‐Pardo et al ., 2020). González‐Ramírez et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results aligned with this study, and it can be suggested that the selective activity might be related to the structure–activity relationship (SAR) of these phlorotannins to Aβ42 oligomers, notably to the fucofuroeckols containing the additional benzofuran ring compared with eckols. This is supported by previous studies demonstrating that benzofuran derivatives have neuroprotective properties against Aβ (Rizzo et al ., 2008; González‐Ramírez et al ., 2018; Lee & Byun, 2018; Cabrera‐Pardo et al ., 2020). González‐Ramírez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Cabrera‐Pardo et al . (2020) explored the multi‐target neuroprotective potential of benzofuran scaffolds and suggested that privileged oxygen‐containing heterocycles such as benzofurans exert neuroprotection by inhibiting several important events involved in the AD process including cholinesterase, ROS stress and Aβ‐cell membrane binding (Rizzo et al ., 2008, 2012; Cabrera‐Pardo et al ., 2020). However, further in‐depth investigations with individual phlorotannins are required to confirm neuroprotective specificity and the chemico‐biological basis conferring neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to design and synthesize compounds that contain two distinct functional groups that each target a different pathway involved in AD ( Cabrera-Pardo et al, 2019 ; Bhatia et al, 2021 ). This can be achieved by the molecular hybridization of different pharmacophore moieties from already identified bioactive molecules ( Uddin et al, 2021 ).…”
Section: Multi-targets: An Unconventional Strategy For Alzheimer’s Di...mentioning
confidence: 99%
“…The benzofuran skeleton can be found in numerous natural molecules [1][2][3] and bioactive compounds. 4,5 The clinical importance of these pharmacophores lies in the fact that they display potent biological properties including antioxidant, 1 antitubercular and antibacterial, 6,7 neuroprotective, 8 anti-inflammatory, 9 and antitumor 10 activities. Due to their diverse biological effects their derivatives are the main source of a great number of clinically approved drugs as well as drug candidates, such as antidepressants citalopram 11 and vilazodone 12 or antiarrhythmic agents amiodaron and dronedarone.…”
mentioning
confidence: 99%